International Journal of Electrical and Computer Engineering: a bibliometric analysis - Yeison Alberto Garcés-Gómez; Vladimir Henao-Céspedes (International Journal of Electrical and Computer Engineering (IJECE), 2022)
This study is focused on analyzing seven years of bibliometric data of the International Journal of Electrical and Computer Engineering (IJECE) from 2014 to 2020. The analysis of 2,928 papers exhibits multi-folded growth of 34.25%, rising from 109 articles in 2014 to 638 articles by 2020. In addition, the analysis of the structure of publications as well as the mapping of bibliographic data based on co-citation, bibliographic coupling, and co-occurrence showed the intellectual structure and connection between universities, countries, and contributing authors. As the journal’s first retrospective, this study not only educates and enriches IJECE’s global readership and aspiring contributors, but may also be useful to its editorial board, as it provides several inputs for navigating future research.